2018
DOI: 10.1063/1.5034499
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation states and thermoelectric properties of BiCuSeO bulks fabricated under Bi or Se deficiencies in the nominal composition

Abstract: We have fabricated the BiCuSeO bulks using raw materials with Bi or Se deficiencies in the nominal composition and investigated crystallographic, chemical compositional, and thermoelectric properties. Owing to the Bi or Se deficiencies in the starting composition, excessive elements and related compounds were deposited as impurity phases and the matrix phase is nearly the stoichiometric BiCuSeO phase. The electrical resistivity, q(T), of the bulks decreases and thermoelectric power, S(T), also decreases with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
2
2
0
1
Order By: Relevance
“…On the other hand, a noticeable amount of impurity phases, Cu 2– x Se (PDF#01-074-1373) and Bi 2 O 3 (PDF#01-088-2043), in the Bi 1– x R x CuSeO samples fabricated with ball milling were detected, they account for less than 3 and 5 vol %, respectively. The appearance of these impurity phases in the samples with ball milling may be a result of Bi or/and Cu deficiency formation as was previously reported. ,, The unit cell parameters for the pristine sample prepared without ball milling are a = 3.92710 Å and c = 8.9278 Å. These values are in good agreement with those reported for samples synthesized by a conventional two-step solid-state reaction .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, a noticeable amount of impurity phases, Cu 2– x Se (PDF#01-074-1373) and Bi 2 O 3 (PDF#01-088-2043), in the Bi 1– x R x CuSeO samples fabricated with ball milling were detected, they account for less than 3 and 5 vol %, respectively. The appearance of these impurity phases in the samples with ball milling may be a result of Bi or/and Cu deficiency formation as was previously reported. ,, The unit cell parameters for the pristine sample prepared without ball milling are a = 3.92710 Å and c = 8.9278 Å. These values are in good agreement with those reported for samples synthesized by a conventional two-step solid-state reaction .…”
Section: Resultssupporting
confidence: 89%
“…The appearance of these impurity phases in the samples with ball milling may be a result of Bi or/and Cu deficiency formation as was previously reported. 30,44,45 The unit cell parameters for the pristine sample prepared without ball milling are a = 3.92710 Å and c = 8.9278 Å. These values are in good agreement with those reported for samples synthesized by a conventional two-step solid-state reaction.…”
Section: ■ Computational Detailssupporting
confidence: 85%
See 1 more Smart Citation
“…Selenium (Se) is an essential element to humans, animals and plant. Se deficiency had been associated with poor immune function, increased risk of mortality, and cognitive decline (Yang et al, 2018;Ishizawa et al, 2018). The research of Lee even revealed that Se could be a cancer-protective agent (Lee, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Температурная зависимость подвижности носителей заряда для Bi 1−x Lax CuSeO (x = 0.02, 0.04, 0.06). На вставке -температурная зависимость подвижности в координатах µ − T1.5 .По нашему мнению, такое изменение транспортных свойств Bi 1−x La x CuSeO может быть обусловлено возникновением дополнительных вакансий висмута при его замещении лантаном, как это было показано в других работах[22][23][24][25]. Наряду со снижением энергии формирования вакансий Bi при допировании исходного соединения (см., например,[25]) наличие фазы CuSe также может…”
unclassified